Endomarketing, organizational commitment and work satisfaction of the collaborators in the Educational Association - Paz Vilchez, José Eber (2020)
This research aims to determine the relationship between Endomarketing, organizational commitment, and employee satisfaction at the Seventh-day Adventist Educational Association of the Northeast Peru Mission, 2019. The scope of the study is correlational with a non-experimental, cross-sectional design, which applied a non-probability sample made up of 125 collaborators, in the five Adventist schools belonging to the Northeast Peru Mission, who applied the Endomarketing questionnaire created by Bhonemberger, the organizational commitment scale created by Meller and Allen and the scale of job satisfaction created by Sonia Palma. The results were analyzed using the Rho Spearman statistical test, demonstrating a considerable positive relationship between Endomarketing and organizational commitment (Rho = 0.870 **; p <0.000), and also analyzed the relationship between Endomarketing and job satisfaction, demonstrating a positive relationship. very strong (Rho = 0.964 **; p <0.000). In conclusion, the greater the Endomarketing practices, the greater the commitment to the educational institution and the greater satisfaction with the collaborators.